The Need for Collective Ijtihad between the Fuqaha and Experts in Health Science and Modern Medicine: A Review - Azhar, Alias (International Journal of Psychosocial Rehabilitation, 2020)
A Fatwa is an answer for rulings in Islam which encompasses rulings that are halal (permissible) or haram (prohibited), harus (neutral) or otherwise, all of which are based on the rulings of the Shariah which are the absolute will of Allah SWT. Fatwas that are issued must go through several steps in research which become the basis of issuing a fatwa. This is to ensure that the ruling given in the issued fatwa truly adheres to the Shariah. Fatwas may also change due to innovations in health sciences and modern medicine. For example, the use of eye drops such as Eye Mo does not nullify the act of fasting since the eyes are not ‘exposed entrances’ into the body. The similar ruling goes for the use of Kohl, (a type of eyeliner) as it does not relieve hunger nor does it quench thirst. Instead, it is applied for health-related benefits. A fatwa was issued that the use of medicine for Angina, which is administered by putting tablets of the medication under the tongue and the use of inhalers for asthmatic people does not invalidate the fast. Health sciences and modern medicine are related very closely to the issue of worship validation. The researcher carried out the study based on two main forms of research, which are; qualitative research and field research. The researcher also applied content analysis to identify the contents and meaning of documents such as the Fatwa Compilation of the National Fatwa Committee (NFC) and their counterparts in each state whether in written form or online. The discussion in this paper includes evaluation towards the concept and approach of collective ijtihad among the Fuqaha (Islamic jurists) as well as experts in medical science to ensure the accuracy of the Fatwas issued. Every ruling will undergo the process of istinbat1 before the form of the ruling is finalized. The practice of issuing fatwas does not only depend on an understanding of rulings in the Shariah but also requires a precise understanding of issues related to health science and modern medicine. Thus, the answer to such rulings must undergo a process of collective ijtihad as a comprehensive approach to issue accurate rulings for questions that arise.